The university of the future in the digital era: digital entrepreneurship education for B40 community in Thailand - Naknawa, Manus; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
Thailand is a country that has very low unemployment when compared to others; it looks good in the big picture but terrible when zooming in. The rural places are most suffering due to lack of education people forced to do any jobs regardless of income or sustainability, and this for themselves not talking about their family from statistics World Bank poverty rate was increasing in 2018. Therefore, provide them with knowledge and skill about being good entrepreneurship is essential to develop and sustain community and (excellent) job opportunities. This paper offers a validated conceptual Malaysian UotF business model. The value proposition of the conceptual business model is to enhance the wellbeing of the B40 community in Thailand through humanizing digital entrepreneurship education activities and harnessing digital capability. The design and system thinking approach has been adopted in this paper to address the wellbeing issues of the B40 community in Thailand through understanding their need, and then followed by building conceptual business models using modeling tools, i.e., Business model canvas (BMC) and Value proposition design canvas (VPC). The approach includes conducting a literature review and interviews for understanding the needs, challenges, and critical problems, formulating and ideating initial business model options in solving the issues, and validation of the initial business model by interviewing the various customer segments.